2016
DOI: 10.1111/risa.12592
|View full text |Cite
|
Sign up to set email alerts
|

Gender Roles and the Expression of Driving Anger Among Ukrainian Drivers

Abstract: The current study investigated the validity of the revised (25-item) version of the driving anger expression inventory (DAX) on a novel sample of 385 drivers from Ukraine. The roles of sex and gender in relation to self-reported aggressive tendencies were also examined. Confirmatory factor analysis supported the four-factor structure of the DAX (adaptive/constructive expression; use of the vehicle to express anger; verbal aggressive expression; and personal physical aggressive expression), and the three aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
5
11
0
Order By: Relevance
“…Although they did not include the DAX, Ozkan and Lajunen (2005) found that masculinity was related to risky and aggressive driving behaviour. This finding is, to some extent, backed up by research in Ukraine, which found that gender-roles, not sex, predicted the expression of driving anger (Sullman, Stephens & Hill, 2016). More specifically, the Ukrainian research found that femininity played a protective role in reducing engagement in aggressive forms of anger expression.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although they did not include the DAX, Ozkan and Lajunen (2005) found that masculinity was related to risky and aggressive driving behaviour. This finding is, to some extent, backed up by research in Ukraine, which found that gender-roles, not sex, predicted the expression of driving anger (Sullman, Stephens & Hill, 2016). More specifically, the Ukrainian research found that femininity played a protective role in reducing engagement in aggressive forms of anger expression.…”
Section: Introductionmentioning
confidence: 84%
“…Although the 25-item version of the DAX is relatively recent, it has been validated in Spain (Gras et al, 2016), Ukraine (Sullman, Stephens & Hill, 2016), along with the Republic of Ireland and the UK . All of these studies have supported the fourfactor structure of the DAX, as have most of the studies using the 49-item version (i.e., Deffenbacher et al, 2002;Esiyok, Yasak & Korkusuz, 2007;Jovanovic, Lipovac, Stanojevic & Stanojevic, 2011;Sarbescu, 2012;Sullman, Stephens & Yong, 2015;Sullman, Stephens & Kuzu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in driving have been explained by different sex-roles (Sullman et al 2016), higher social acceptance of male risk taking by society and an evolutionary based gender identity (Özkan and Lajunen 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The original version of the questionnaire was developed in English, and then translated into South Korean and Japanese by a professional translator as per the standards followed by previous researchers (e.g. Sullman et al, 2017). Back translation using the procedure of Hohl and Gaskell (2008) was applied to ensure consistency of meaning.…”
Section: Methodsmentioning
confidence: 99%